2013
DOI: 10.4103/2229-5178.110625
|View full text |Cite
|
Sign up to set email alerts
|

Nerve damage in leprosy: An electrophysiological evaluation of ulnar and median nerves in patients with clinical neural deficits: A pilot study

Abstract: Background:Leprosy involves peripheral nerves sooner or later in the course of the disease leading to gross deformities and disabilities. Sadly, by the time it becomes clinically apparent, the nerve damage is already quite advanced. However, if the preclinical damage is detected early in the course of disease, it can be prevented to a large extent.Materials and Methods:We conducted an electrophysiological pilot study on 10 patients with clinically manifest leprosy, in the Dermatology Department of Mahatma Gand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
18
0
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 11 publications
3
18
0
4
Order By: Relevance
“…Present study showed marked changes in all nerve conduction parameters in median and ulnar nerves which are suggestive of mixed axonal-demyelinating type of neural damage of both sensory and motor fibres. Similar findings were observed by Kar et al, Maharatta et al, Chaurasia et al, Husain et al 1,2,5,9,11 There are certain causes for the occurrence of multiple changes in NCS, even in newly diagnosed cases at our center, viz. prevalent illiteracy among study population and attached social stigma with the disease, making the presentation late.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Present study showed marked changes in all nerve conduction parameters in median and ulnar nerves which are suggestive of mixed axonal-demyelinating type of neural damage of both sensory and motor fibres. Similar findings were observed by Kar et al, Maharatta et al, Chaurasia et al, Husain et al 1,2,5,9,11 There are certain causes for the occurrence of multiple changes in NCS, even in newly diagnosed cases at our center, viz. prevalent illiteracy among study population and attached social stigma with the disease, making the presentation late.…”
Section: Discussionsupporting
confidence: 89%
“…Peripheral neuropathy in leprosy varies from as small as, involvement of an intradermal nerve in the cutaneous patches to as large as major lesion in the peripheral or cranial nerve trunk. 1 This silent neuropathy starts with blockade of nerve impulse and then leads to visible pathological changes. 2 Cranial nerve involvement like facial, trigeminal or other nerves is also commonly seen in patients with leprosy.…”
Section: Introductionmentioning
confidence: 99%
“…Serious injury may occur in the peripheral nerves of leprosy patients, including sensory and motor disturbances and deformities [18]. However, in our study, lesions were not observed in peripheral nerves, as supported by data on the use of adaptation and disability level ( Table 2).…”
Section: Discussionsupporting
confidence: 62%
“…Potenciais near-nerve captados de fibras de seis micrômetros de diâmetro podem estar anormais quando o estudo da condução convencional está normal (MARQUES et al, 2003). Envolvimento do sistema autonômico pode ser documentado em pacientes com a forma virchoviana pela medida da resposta simpática da pele e medidas da frequência cardíaca durante a respiração profunda (BROWN et al, 1996b MOUTON et al, 1999) e da hanseníase (JARDIM et al, 2003;KAR et al, 2013;SANTOS et al, 2017). A mononeuropatia múltipla é um tipo de neuropatia periférica que compromete mais de um tronco nervoso com distribuição temporal e topográfica não uniforme.…”
Section: Análise Das Variáveis Da Condução Nervosaunclassified
“…33% e apenas três pacientes com polineuropatia como a forma clínica Kar et al (2013). relataram esse padrão em oito dos dez pacientes avaliados e dois pacientes com padrão de polineuropatia Jardim et al (2004).…”
unclassified